System rządów parlamentarnych na obszarze poradzieckim: casus Mołdawii i Łotwy - Fedorowicz, Krzysztof (Wydawnictwo Naukowe Wydziału Nauk Politycznych I Dziennikarstwa UAM w Poznaniu, 2012)
The fundamental problem faced by the states that have emerged in the area of the former USSR involved the definition of the desired form of their own political regime. The choices made in this respect in the first stage of political transformation were frequently limited only to the formal stipulation of model legal and constitutional solutions. The post-communist elite wielding power in the new states was characterized by a desire to form a one-man organ of state in the form of a strong president. The absence of democratic traditions and the negative legacy of the USSR have profoundly influenced the processes of shaping the political regimes in the post-Soviet area, and have actually become the predominant reason to legitimize authoritarianism. Only a few states of the former USSR have decided to adopt a model of governance other than a strong presidential system. Latvia deserves attention in this respect, as it has decided to reinstate the tested political principles of the interwar period. In the process of political transformation, the Latvian political elite has opted for the parliamentary system of governance and chose a weak presidency and the primacy of parliament. The transformation process was quickly completed allowing Latvia to be classified today as a non-consolidated democracy. Moldova’s adopting the system of parliamentary governance in 2000 was, in turn, an unintentional result of a political conflict caused by the President’s endeavors to form a strong presidential system. Moldovan parliamentarianism is a product of a protracted shaping of the institutional foundations of the political system and a byproduct of political competition between the legislative and executive powers. The domination of Communists on the Moldovan political stage, however, resulted in the state’s appropriation by one group and President Vladimir Voronin, who enjoyed a great influence exerted both on the parliamentary majority (as the leader of the ruling party) and the government, despite the formal system providing for a parliamentary republic. There emerged a dangerous precedent of the President exceeding his rights and thus becoming the actual leader of a formally parliamentary republic. In the period from 2001–2009, Moldova was a system of controlled democracy where apparently democratic institutions were in fact a cover for undivided, informal power wielded by a small circle. This triggered a social revolution in 2009 and early parliamentary elections, which resulted in a transfer of power and the establishment of a coalition of liberal and democratic parties clearly expressing their intention to implement market reforms and European integration. Despite political obstruction in Moldova’s shaping of its political system, the country stands out among the former post-Soviet republics. It is the only state in the Commonwealth of Independent States where a continuous and uninterrupted cycle of the transfer of power by means of elections can be observed to conform to the law and constitution since the country declared independence in 1991.
Keywords: parlamentaryzm; system polityczny; obszar poradziecki